A Study of Consumer’s Buying Pattern of Cosmetic Products in South Haryana - Kaushik, Neeraj; Gupta, Deepak (Indian Journal of Marketing, 2009)
The Indian cosmetics and personal care industry has been growing at a rate of 15-20 percent. But still the market penetration of cosmetics and toiletries products in India is meager. The cosmetic companies are now eyeing the small cities as it is an untapped market and present vast opportunities. The present study attempts to study the buying pattern of consumers and the impact of demographic variables thereon. Results indicate that The prime reason for using cosmetics was ’to look appealing’ followed by ’to be with current trends’. Quality and Price were found to be the most important criterion for buying cosmetics.